The cruel birth of Bangladesh : memoirs of an American diplomat - Blood, Archer K. (Dhaka : University Press Limited, 2002)
An account of political events prior to the creation of Bangladesh; covers the 1970-1971 period.
Includes bibliographical references (pages [361]-363) and index.
GenEd
Keywords: Bangladesh -- Politics and government